The new extended rational SGEEM for construction of optical solitons to the (2+1)-dimensional Kundu-Mukherjee-Naskar model - Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Walter de Gruyter Gmbh, 2019)
This work proposes the new extended rational sinh-Gordon equation expansion technique (SGEEM). The computational approach is formulated based on the well-known sinh-Gordon equation. The proposed technique generalizes the sine-Gordon/sinh-Gordon expansion methods in a rational format. The efficiency of the suggested technique is tested on the (2+1) imensional Kundu ukherjee askar (KMN) model. Various of optical soliton solutions have been obtained using this new method. The conditions which guarantee the existence of valid solitons are given.
Keywords: New extended rational SGEEM; KMN model; optical solitons